The Global Quest to Build World‐Class Universities: Toward a Social Justice Agenda. Issue 168 (December 2014) - Rhoads, Robert A.; Li, Shuai; Ilano, Lauren
Abstract : This chapter provides a critical perspective on the global quest to build world‐class universities (WCUs), including global "ranking mania, " excessive emphasis on university branding, and the attending threats to the traditional public good mission of the university. Alternatively, we offer suggestions on how rankings may be used to advance a social justice vision of WCUs.